Intrauterine transplantation of autologous menstrual blood stem cells increases endometrial thickness and pregnancy potential in patients with refractory intrauterine adhesion. Issue 11 (27th August 2020) - Ma, Hailan; Liu, Mengting; Li, Yufeng; Wang, Wei; Yang, Keqin; Lu, Lanying; He, Mei; Deng, Taoran; Li, Meiling; Wu, Dongcheng
Abstract: Aim: This study was designed to evaluate the effects of intrauterine transplantation of menstrual blood stem cells (MenSCs) on endometrial thickness and pregnancy outcomes in patients with refractory intrauterine adhesion (IUA). Methods: This study included a group of infertile women ( n = 12, age 22–40 years), with refractory IUA. Autologous MenSCs isolated from the women's menstrual blood were expanded in vitro and transplanted into their uteruses, followed by hormone replacement therapy. Transvaginal ultrasound examination was performed to assess the endometrial thickness. Transabdominal ultrasound was conducted to detect pregnancy outcome. Results: Autologous MenSCs were successfully isolated and expanded from menstrual blood and transplanted into the uterus of each patient. A significant improvement of the endometrial thickness was observed from 3.9 ± 0.9 to 7.5 ± 0.6 mm ( P  < 0.001). No adverse reaction was observed. The duration of menstruation was increased from 2.4 ± 0.7 to 5.3 ± 0.6 days ( P  < 0.001). Five out of 12 patients achieved clinical pregnancy and the pregnancy rate was 41.7%. Conclusions: Intrauterine transplantation of autologous MenSCs results in regeneration of endometrium, a prolongation of menstrual duration and an increase rate of pregnancy in patients with refractory IUA.